Multiresidue Method for Quantification of Sulfonamides and Trimethoprim in Tilapia Fillet by Liquid Chromatography Coupled to Quadrupole Time-of-Flight Mass Spectrometry Using QuEChERS for Sample Preparation - Kátia S. D. Nunes; Márcia R. Assalin; José H. Vallim; Claudio M. Jonsson; Sonia C. N. Queiroz; Felix G. R. Reyes (Journal of Analytical Methods in Chemistry)
A multiresidue method for detecting and quantifying sulfonamides (sulfapyridine, sulfamerazine, sulfathiazole, sulfamethazine, sulfadimethoxine, sulfamethoxazole, and sulfamethoxypyridazine) and trimethoprim in tilapia fillet (Oreochromis niloticus) using liquid chromatography coupled to mass spectrometry was developed and validated. The sample preparation was optimized using the QuEChERS approach. The chromatographic separation was performed using a C18 column and 0.1% formic acid in water and acetonitrile as the mobile phase in the isocratic elution mode. Method validation was performed based on the Commission Decision 2002/657/EC and Brazilian guideline. The validation parameters evaluated were linearity (r ≥ 0.99); limits of detection (LOD) and quantification (LOQ), 1 ng·g−1 and 5 ng·g−1, respectively; intraday and interdays precision (CV lower than 19.4%). The decision limit (CCα 102.6–120.0 ng·g−1 and 70 ng·g−1 for sulfonamides and trimethoprim, respectively) and detection capability (CCβ 111.7–140.1 ng·g−1 and 89.9 ng·g−1 for sulfonamides and trimethoprim, respectively) were determined. Analyses of tilapia fillet samples from fish exposed to sulfamethazine through feed (incurred samples) were conducted in order to evaluate the method. This new method was demonstrated to be fast, sensitive, and suitable for monitoring sulfonamides and trimethoprim in tilapia fillet in health surveillance programs, as well as to be used in pharmacokinetics and residue depletion studies.